2016
DOI: 10.1167/iovs.15-18358
|View full text |Cite
|
Sign up to set email alerts
|

Local Modulation of Retinal Vein Tone

Abstract: PURPOSE. To determine whether vascular tone of isolated porcine retinal veins can be modulated by tissue-generated vasoactive factors such as endothelin-1 and adenosine. Such information may be useful in understanding the role of the retinal veins in regulating blood flow, and also provide a model for investigating new hypotheses suggesting a role for vasoactive factors in retinal vascular diseases such as retinal vein occlusion.METHODS. An isolated perfused retinal vein preparation was used for this study. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…However, it has been shown that retinal veins have a rich coat of glial cells. 25 Yu et al 17 recently showed that ET-1 and adenosine could effectively induce vasoconstriction and vasodilation in porcine retinal veins without any identifiable smooth muscle cells (SMCs). Thus, the removal of glial activity on the retinal vein via LAA may account for the increased venous diameter and suggest the possibility that glial cells are able to produce a vasomotor effect independent of SMCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that retinal veins have a rich coat of glial cells. 25 Yu et al 17 recently showed that ET-1 and adenosine could effectively induce vasoconstriction and vasodilation in porcine retinal veins without any identifiable smooth muscle cells (SMCs). Thus, the removal of glial activity on the retinal vein via LAA may account for the increased venous diameter and suggest the possibility that glial cells are able to produce a vasomotor effect independent of SMCs.…”
Section: Discussionmentioning
confidence: 99%
“…16 A recent study provides evidence that retinal veins without identifiable smooth muscle cells can be modulated by vasoconstricting and vasodilating agents. 17 Thus, there is growing evidence that retinal veins are under some form of local autoregulation.…”
mentioning
confidence: 99%
“…In adult retinas, arteries and veins are both covered in smooth muscle (Ehling et al, 2013), and these may be more effective at regulating vessel diameter than the pericytes covering the capillaries. Retinal vasculature is subject to metabolic regulation (Pournaras et al, 2008), and although the smooth muscle layer around retinal veins is thinner and less organised than arteries, there is evidence that it is capable of vasoconstriction (Yu et al, 2016). The functional consequence of increased EC density and capillary diameter on retinal vascular function and metabolic regulation in particular deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has shown that isolated porcine retinal veins are reactive to local vasoactive factors such as vasodilator adenosine and vasoconstrictor endothelin-1 (ET-1). 9 It is unclear, however, whether smaller upstream venules exhibit similar reactivity, especially vasoconstriction, which dictates not only blood drainage but also capillary pressure and fluid exchange.…”
mentioning
confidence: 99%